Predictors of Successful Downstaging of Hepatocellular Carcinoma Outside Milan Criteria. Issue 11 (November 2016) - Murali, Arvind R.; Romero-Marrero, Carlos; Miller, Charles; Aucejo, Federico; Levitin, Abraham; Gill, Amanjit; McLennan, Gordon; Karuppasamy, Karunakaravel; Zein, Nizar N.; Lopez, Rocio; Menon, K.V. Narayanan
Abstract : Background: Patients with hepatocellular carcinoma (HCC) outside Milan criteria (MC) may be candidates for liver transplantation (LT) after successful downstaging. Factors that predict successful downstaging are unclear. We aimed to identify the predictors of successful downstaging of HCC in patients outside MC. Methods: We performed a retrospective cohort study on consecutive patients with HCC outside MC who received downstaging with locoregional therapy. Clinical and laboratory variables, tumor characteristics including total tumor volume (TTV) and up-to-7 criteria were recorded. We performed univariate and multivariate logistic regression analyses to identify variables associated with successful downstaging. Results: Of 675 patients with HCC, 90 patients outside MC received downstaging. Fifty-three (59%) patients were successfully downstaged, 37 (41%) failed downstaging. University of California at San Francisco criteria, α-fetoprotein, up-to-7 criteria, TTV, and platelet count were predictors of successful downstaging on univariate analysis. Total tumor volume was an independent predictor of successful downstaging on multivariate logistic regression ( P = 0.04, area under receiver operating characteristic curve 0.89 (95% confidence interval, 0.82-0.96). Fifty-two (76%) of 68 patients with TTV less than 200 cm 3 were successfully downstaged, whereas only 1 (4.5%) of 22 patients with TTV greater than 200 cm 3 were successfully downstaged. Forty-five (50%) patients underwent LT. Kaplan-Meier survival rates at 1 and 5 years post-LT were 95.3% and 79.4%, respectively. Patients who were successfully downstaged had better survival than patients who failed downstaging ( P < 0.01). Conclusions: Total tumor volume is a good predictor of successful downstaging of HCC. Patients with TTV less than 200 cm 3 may be considered good candidates for downstaging. Further studies with larger cohort of patients are needed to validate this approach in patients with HCC outside Milan. Abstract : The authors report on the analysis of 90 patients subjected to down staging of HCC outside Milan. They identified several features including total tumor volume as predictors of successful down staging into Milan in this cohort of transplant candidates.